Pembagian Harta Bersama Akibat Perceraian Menurut Hukum Islam: Kajian terhadap Putusan Pengadilan Agama Yogyakarta Nomor 0297/Pdt.G/2017/PA - Moch Azam Azhari (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
All God's creatures, including humans, pets, and other animals and plants, are covered by the general sunnatullah of marriage. This is the way that Allah SWT chose for His creatures to reproduce and maintain their lives. The problem of the property of each husband and wife is one of the legal consequences of marriage. Article 35 of the Marriage Law regulates joint property. Marital assets are also obtained as joint assets. In the Compilation of Islamic Law, it is stated in Article 1 letter (f) that